Legal Position Artificial Intelligence Art Generator in Copyright Law - Ananto, Muhammad Mizan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Artificial Intelligence (AI) art generators are disrupting the meaning of creating an artwork that has long been known. The AI art generator has features that make it easy for users to create images, simply by entering text descriptions, then the AI will produce the desired image. This creation process then raises questions about the legal position of AI on copyright contained in the image. This study discusses the legal position of AI in intellectual property law by dividing it into two options: First, how is the prospect of recognizing AI as a legal subject of copyright law, and secondly how existing law can accommodate AI as an object of copyright law. The study found that there are opportunities for AI to be recognized as a copyright subject by equating its position as a legal entity. Another alternative option is to view AI as an object of copyright only, with the note that there needs to be proof regarding originality as a requirement for copyright protection.